Optimization of Sound Transmission Loss through a Thin Functionally Graded Material Cylindrical Shell - Ali Nouri; Sohrab Astaraki (Shock and Vibration)
The maximizing of sound transmission loss (TL) across a functionally graded material (FGM) cylindrical shell has been conducted using a genetic algorithm (GA). To prevent the softening effect from occurring due to optimization, the objective function is modified based on the first resonant frequency. Optimization is performed over the frequency range 1000–4000 Hz, where the ear is the most sensitive. The weighting constants are chosen here to correspond to an A-weighting scale. Since the weight of the shell structure is an important concern in most applications, the weight of the optimized structure is constrained. Several traditional materials are used and the result shows that optimized shells with aluminum-nickel and aluminum-steel FGM are the most effective at maximizing TL at both stiffness and mass control region, while they have minimum weight.